Bioaccumulation of selected metals in the blood cockle (Anadara granosa) from Langkawi Island, Malaysia - Md Suhaimi, Mohd Zahir; Yunus, Kamaruzzaman; John, Akbar; Khan Chowdhury, Ahmed Jalal; Saad, Shahbudin; Said, Mohd Al-Barwani; Stephen J., Goddard (Oriental Scientific Publishing Company, Inc., 2011)
Concentration of metals (Zn, Cu and Pb) in the edible portion of commercially important blood cockle (Anadara granosa) collected from Langkawi Island, Malaysia was analyzed. Samples were collected from 3 different stations namely Kuah (KU), Kuala Triang (KT) and Pantai Kok (PK) during 2009. Heavy metal concentrations were detected using Inductively Coupled Plasma Mass Spectrometry (ICP-MS) with respect to the total body burden (ie., the observed concentration multiplied with total flesh weight). The observed mean concentration of Zn, Cu and Pb at Kuah station was 110.75 μg/g, 12.35 μg/g and 1.73 μg/g respectively followed by Kuala Triang station with mean Zn, Cu and Pb concentration of 62.16 μg/g, 6.72 μg/g and 0.06 μg/g respectively. The lowest concentration of selected metals was observed in the samples collected from Pantai Kok station with mean Zn, Cu and Pb concentrations of 77.50 μg/g, 8.56 μg/g and 0.04 μg/g respectively. The calculated Bio-concentration Factor Value (BCFsample-sediment) showed the resisting the entry of metals or limited ability of A.granosa in accumulating selected metals from their environment as indicated by the BCFsa-se value (< 1) except the Zn accumulation from Kuah station (BCFsa-se value = 2.21). However, the observed metal concentration in the sample tissue was lower than the national and International permissible standard limit for human consumption.